KEDUDUKAN HUKUM REKOMENDASI DEWAN PERWAKILAN RAKYAT DAERAH DALAM PELAKSANAAN PEMBANGUNAN DI DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 2015 PERUBAHAN KEDUA ATAS UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Alfhadri Maulana; Ikhsan '; Dessy Artina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Local government administrators are Local Government and DPRD. In the framework of local governance that local government and DPRD together but in different duties and functions. The combination and duty of the local government together with the DPRD is a manifestation of the implementation of local government. So the local government with the DPRD should be able to function according to their respective duties so that the realization of good regional government and sustainable development of the region. In some instances, development in the regions is sometimes required by the legislature to be involved and strengthen the capacity to implement a development. Recommendations are also needed when identifiable obstacles or challenges that can not find a solution so that development becomes impeded.The type of research used in the writing of this law is a normative legal research that focuses on the principles by formulating legal principles, both from social data and from positive written legal data. While viewed from the nature of this research is descriptive. This study uses secondary data that is ready-made data.The result of this study is the recommendation of DPRD in the implementation of regional government is not an elaboration of the authority of DPRD oversight of local government. The DPRD recommendation in the regional development process is a constitutional convention in the administration of the State government. The DPRD recommendation in its implementation has two functions, namely the function of the requirements and the confirmation function. In the requirements function, recommendation is a requirement of issuing government decisions. In the confirmation function, the DPRD recommendation is merely an instrument of non-binding approval in the publication of government decisions.Keywords: recommendation of DPRD, local government.